TINJAUAN TENTANG TATA RIAS PENGANTIN ADAT MANDAILING DI KECAMATAN LEMBAH MELINTANG KABUPATEN PASAMAN BARAT - Zerti Okveriza; Vivi Efrianova (Jurnal Tata Rias dan Kecantikan, 2022)
Mandailing traditional bridal makeup in West Pasaman Regency needs to be studied because there is a mixing of two cultures between minangkabau culture and mandailing culture, in order to produce a clear and concrete picture of mandailing bridal makeup in  Pasaman. This study aims 1)to describe the shape and equipment of bridal makeup mandailing, 2) to describe the work process of bridal makeup mandailing, 3) to reveal what are the meanings of clothing and makeup equipment mandailing bride in West Pasaman Regency. This study uses a qualitative approach. Informant networking is done using snowball sampling technique. This research instrument is the researcher himself and assisted with supporting instruments such as tape rekorder, video tape, camera. Data collection techniques are carried out by observation, interviews and documentation. The steps of analyzing data are data collection, data reduction, data presentation and conclusion drawing. The results showed  1) The form of wedding dress on bridal makeup aadat mandailing in Nagari Ujung Gading, consisting of codecs / songket, basiba kuruang shirts from minang, shawl or Ulos from mandailing, with equipment consisting of golden moong, jagar-jagar and jarunjung, suri moon necklace, belt or bobat, puttu daboru bracelet, hissik bracelet, long nails, kris and tarompa. For the form of the groom's dress consists of a black biludru suit, sarawa gadang / lapang black, sesamping, and shawl or Ulos mandailing, with perengkapan such as hampu or ampu, belt, large plain bracelet, kris and tarompah. 2) The Process of Bridal Makeup Mandailing in Nagari Ujung Gading District Transverse Valley West Pasaman Regency. 3) The meaning of the form of clothing and bridal makeup equipment mandailing custom in Nagari Ujung Gading as a whole is for each use of minang clothing and mandailing equipment can only be worn by brides who carry out medium helatan or large helat. By fulfilling some provisions in "Sepanjang Adat Nagari". One of them is in slaughtering animals for helat. For medium helat animals sacrificed in the form of goats and for large helat in the form of buffalo animals. In this case it relates to the type of headdress (bulang) that the bride will wear. For medium helat bulang used is a five-tiered bulang or so-called bambeng (goat). And for large helat, the bulang used is a seven-storey bulang or called bulang barbo (buffalo). It is recommended to be able to maintain and preserve the existence of traditional bridal clothing and equipment mandailing.